Higher single dose of bortezomib plus thalidomide and dexamethasone is a promising therapy for newly diagnosed multiple myeloma - Xu, Peipei; Zhou, Rongfu; Xu, Jingyan; Ouyang, Jian; Shao, Xiaoyan; Chen, Bing (Translational Cancer Research, 2019)
Background: Bortezomib in combination with thalidomide and dexamethasone (VTD) has been widely used for newly diagnosed multiple myeloma (MM). The aim of this study was to evaluate the efficacy and safety of a new high-dose bortezomib plus thalidomide and dexamethasone as an induction and consolidation therapy regimen for MM. Methods: A total of 93 patients with previously untreated symptomatic MM were enrolled in this single-center study. In group-1, 40 patients received bortezomib 1.6 mg/m2 and dexamethasone 40 mg on days 1, 6 and 11, plus thalidomide 100 mg on days 1–21 (VTD-1). In group-2, 53 patients received bortezomib 1.3 mg/m2 and dexamethasone 40 mg on days 1, 4, 8 and 11 in combination with thalidomide 100 mg on days 1–21 (VTD-2). Results: The odds ratio rates after 2 cycles of VTD and the best response during this study were 95% vs. 81.1% (P=0.044), and 95% vs. 90.6% (P=0.349) in group-1 and group-2, respectively. The best CR rate in group-1 was higher than that in group-2 [52.5% vs. 45.3% (P=0.316)]. In group-1, only 2 of 21 patients who achieved CR relapsed from the disease, as did 9 of 24 patients in group-2 (P=0.031). The median PFS in group-1 and group-2 were 34 and 28.8 months (P=0.969), and the median OS in group-1 and group-2 were 33.5 and 46.4 months (P=0.987). In group-1 and group-2, the median CD34+ cells of stem cell collection were 3.68×106 vs. 5.84×106 cells/kg (P=0.179). Patients in group-1 had a lower incidence of peripheral neuropathy than group-2 [32.5% vs. 41.5% (P=0.371)]. Conclusions: High-dose bortezomib at a dose of 1.6 mg/m2 in combination with thalidomide and dexamethasone was well tolerated and highly efficient as an induction and consolidation therapy for MM.